2007
DOI: 10.1160/th07-04-0248
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide bond disruption by a β3-Cys549Arg mutation in six Jordanian families with Glanzmann thrombasthenia causes diminished production of constitutively active αIIbβ3

Abstract: SummaryαIIbβ3 integrin mediates platelet aggregation following its activation. Its absence or dysfunction causes Glanzmann thrombasthenia (GT), an inherited bleeding disorder that is rare worldwide but relatively frequent in several populations with high rates of consanguinity, including Arabs in Israel and Jordan. Cysteine residues in the β3 epidermal growth factor (EGF) domains are involved in αIIbβ3 formation and activation. In this study we present a novel Cys549Arg mutation in β3 identified in six Jordani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(1 citation statement)
references
References 38 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Cysteine residues in the extracellular domain are correlated with the integrin structure. Mutations in the conserved cysteines in the EGF domains of the β 3 lower leg have been found to cause extension (Kamata et al, 2004; Mor‐Cohen et al, 2007). Indeed, sequence alignment has shown that, compared with other β integrins, β 8 lacks two pairs of conserved cysteines that form disulfide bonds within the EGF3 and β‐tail domains, rendering β 8 unable to stabilize its bent conformation (Cormier et al, 2018).…”
Section: Integrin αVβ8 Structurementioning
confidence: 99%
“…Cysteine residues in the extracellular domain are correlated with the integrin structure. Mutations in the conserved cysteines in the EGF domains of the β 3 lower leg have been found to cause extension (Kamata et al, 2004; Mor‐Cohen et al, 2007). Indeed, sequence alignment has shown that, compared with other β integrins, β 8 lacks two pairs of conserved cysteines that form disulfide bonds within the EGF3 and β‐tail domains, rendering β 8 unable to stabilize its bent conformation (Cormier et al, 2018).…”
Section: Integrin αVβ8 Structurementioning
confidence: 99%